Avaliação de aprendizagem nas aulas de educação física do Instituto Federal do Pará Campus Belém - CONEGUNDES, Lucas Araújo (2022)
This study addresses the learning assessment performed by Physical Education teachers of the Federal Institute of Pará Campus Belém in order to understand the assessment in the context of school physical education. The results obtained in this research, through questionnaire and interview, show that the practice of some teachers about evaluation in School Physical Education differs in some points to those recommended by Law 9394/96 - Law of Guidelines and Bases of National Education. The practice of assessment in Physical Education in a classificatory way aimed at physical fitness can still be identified in some teaching practices. This study aimed to analyze the assessment methods that are used by teachers, interrelating them with the objectives of the teaching-learning process, focusing their thoughts on the critical-overcoming perspective of Physical Education, which aims at an assessment where the focus is on critical assimilation of the student about the taught content.